A Novel GABA-Producing Levilactobacillus brevis Strain Isolated from Organic Tomato as a Promising Probiotic - Asia Pizzi; Carola Parolin; Davide Gottardi; Arianna Ricci; Giuseppina Paola Parpinello; Rosalba Lanciotti; Francesca Patrignani; Beatrice Vitali (Biomolecules, 2025)
Gamma-aminobutyric acid (GABA) is a non-protein amino acid playing a significant role in the central nervous system and the gut–brain axis. This study investigated the potential to produce GABA by lactic acid bacteria (LAB) isolated from different varieties of organic tomatoes. The isolated LAB were taxonomically identified by 16S rRNA gene sequencing, the presence of the gadB gene (glutamate decarboxylase) was detected, and GABA production was quantified using HPLC. Levilactobacillus brevis CRAI showed the highest GABA production under optimised fermentation conditions with 4% monosodium glutamate (MSG). The genome sequencing of L. brevis CRAI revealed the presence of gadA and gadB isoforms and assessed the strain’s safety profile. The gene expression analysis revealed that the gadA and gadB genes were upregulated in the presence of 4% MSG. The probiotic potential of L. brevis CRAI was also assessed by functional assays. The strain showed strong antimicrobial activity against representative enteropathogens, i.e., Escherichia coli ETEC, Salmonella choleraesuis, and Yersinia enterocolitica, and anti-inflammatory effect, reducing nitric oxide production in LPS-stimulated RAW264.7 macrophages. In addition, its ability to adhere to intestinal epithelial Caco-2 cells was demonstrated. These results highlight L. brevis CRAI as a promising candidate for the development of GABA-enriched functional foods or probiotic supplements with the perspective to modulate the gut-brain axis.